El poblamiento tardorromano en Alicante a través de los testimonios materiales: estado de la cuestión y perspectivas - Gutiérrez Lloret, Sonia (Antigüedad y Cristianismo, 1998)
Reflections on the general character of the investigations on the last phases of Roman culture. History of the investigations. Studies of the materials. A view of the urban and rural settlements and of the necropolis in the areas that now belog to the province of Alicante. As we know very little about this region at this time any investigation, however small, will be valuable.